Mathematical simulation of connective heat transfer of boundary turbulent flows - Лунис, М. (Proceedings of National Aviation University (archive), 1998)
Proposed is the method of simulation of turbulent boundary flows with connective heat transfer which develop both near flat surfaces and in channel. With the help of algebraic model of turbulent viscosity coefficient and heat transfer received were digital and approximate-analytical solutions of conservations equations the results of which correspond to the experimental data of board range of Reinholds and Prandtl numbers